2019
DOI: 10.3390/v11060577
|View full text |Cite
|
Sign up to set email alerts
|

Novel Victorivirus from a Pakistani Isolate of Alternaria alternata Lacking a Typical Translational Stop/Restart Sequence Signature

Abstract: The family Totiviridae currently contains five genera Totivirus, Victorivirus, Leishmavirus, Trichomonasvirus, and Giardiavirus. Members in this family generally have a set of two-open reading frame (ORF) elements in their genome with the 5′-proximal ORF (ORF1) encoding a capsid protein (CP) and the 3′-proximal one (ORF2) for RNA-dependent RNA polymerase (RdRp). How the downstream open reading frames (ORFs) are expressed is genus-specific. All victoriviruses characterized thus far appear to use the stop/restar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 68 publications
1
29
0
Order By: Relevance
“…The third element of the -1 frameshifting mechanism is a short spacer region between the slippery site and the pseudoknot, and is a 19 nt long stretch in TkTV1/Mg10. It was recently demonstrated that the presence of -1 ribosomal frameshifting elements does not necessarily lead to the expression of a fusion protein (Jamal et al, 2019). Although the expression of a CP-RdRp fusion protein by TkTV1 is yet to be confirmed experimentally, the presence of the -1 frameshifting signature in TkTV1 genome might induce the expression of an ORF1-ORF2 (CP-RdRp) fusion protein of 1518 aa with a molecular weight of 172.020 kDa.…”
Section: Resultsmentioning
confidence: 99%
“…The third element of the -1 frameshifting mechanism is a short spacer region between the slippery site and the pseudoknot, and is a 19 nt long stretch in TkTV1/Mg10. It was recently demonstrated that the presence of -1 ribosomal frameshifting elements does not necessarily lead to the expression of a fusion protein (Jamal et al, 2019). Although the expression of a CP-RdRp fusion protein by TkTV1 is yet to be confirmed experimentally, the presence of the -1 frameshifting signature in TkTV1 genome might induce the expression of an ORF1-ORF2 (CP-RdRp) fusion protein of 1518 aa with a molecular weight of 172.020 kDa.…”
Section: Resultsmentioning
confidence: 99%
“…The complete genome sequence of PjPmV1 was determined by next-generation sequencing (NGS) and Sanger sequencing. We performed NGS (HiSeq 2500, Illumina, Inc.) as previously described (Jamal et al, 2019;Shamsi et al, 2019). For NGS, we submitted a mixed dsRNA preparation (called "pool A1") from three fungal strains including P. janthinellum strain A58 and Alternaria alternata strain A16 (Jamal et al, 2019).…”
Section: Extraction Sequencing and Northern Hybridization Of Dsrnamentioning
confidence: 99%
“…We performed NGS (HiSeq 2500, Illumina, Inc.) as previously described (Jamal et al, 2019;Shamsi et al, 2019). For NGS, we submitted a mixed dsRNA preparation (called "pool A1") from three fungal strains including P. janthinellum strain A58 and Alternaria alternata strain A16 (Jamal et al, 2019). The 5'-and 3'-terminal nucleotide sequences were determined by 3' RNA ligase-mediated rapid amplification of cDNA ends (3' RLM-RACE) using dsRNA as templates with the method of Lin et al (2013).…”
Section: Extraction Sequencing and Northern Hybridization Of Dsrnamentioning
confidence: 99%
See 1 more Smart Citation
“…Almost all victoriviruses infect their natural hosts without any apparent symptoms; examples include Rosellinia necatrix victorivirus 1 and Alternaria alternata victorivirus 1 (Chiba et al, 2013a;Jamal et al, 2019). Exceptions include Helminthosporium victoriae virus 190S, which induces disease symptoms in its natural host H. victoriae (Xie et al, 2016).…”
Section: Discussionmentioning
confidence: 99%